Value relevance of accounting information in selected Middle East countries - Khanagha, Jamal Barzegari (2010)
In the past, stock markets in the Middle East have been widely ignored by international investors due to imposed limitations on foreign stock ownership, the lack of common accounting standards and corporate transparency, or they have been simply dismissed on the basis of economic and political uncertainty. Currently, most of the Middle East countries had some economic reforms and structural adjustment programs (e.g. changes on institutional setting and regulations such as establishing security market regulation, investor protections, trading rules based on shared regulatory responsibility, etc.). Following improvements in financial markets, the Middle East accounting standards have also been reformed to improve the quality of accounting information. Thus, the role of the Middle East stock exchanges have recently become more effective in the international financial system due to the efforts made to increase development in the areas of financial markets, accounting and economic growth. Despite their effective role, the review of literature showed that there is no comprehensive study to identify the value relevance of accounting information and effects of accounting reforms in this region. This study investigates the value relevance of accounting information through three main objectives a) determine the value relevance of accounting information in selected Middle Eastern countries, b) investigate the effect of reform and enforcement of accounting standards in the selected Middle East markets and c) investigate the effect of different classifications of transaction on value relevance of cash flow statement in the Middle Eastern countries. The study uses both the regression-variations and the portfolio-returns approaches to measure the value relevance. Using both approaches provides different perspective on the issue of value relevance of accounting information. Overall, the findings in selected countries showed that firstly, accounting information in all of selected countries is value relevant. Secondly, the results for each country showed, there is a significant difference in value relevance between the periods before and after reform. In other words, accounting standards reforms had impact on the value relevance of accounting information in all of the selected countries. The results showed that accounting standards reforms have improved value relevance of accounting information in Bahrain and Saudi Arabia’s stock exchanges, while for the UAE and Iran reforms did not improve value relevance of accounting information. The results of control variables for selected countries indicated difference in value relevance of accounting information in large and small companies. Findings also revealed greater value relevancy of accounting information of small companies in Bahrain, UAE, and Iran than the large companies, whereas for Saudi Arabia the results are reverse. Results in selected countries revealed differences in value relevance of accounting information in different industries. The results also indicated that information content of cash flow statements based on International Financial Reporting Standards (IFRS) is more value relevant than statement based on the Financial Accounting Standards Board (FASB). Overall, the relevancy of accounting information in selected countries is consistent with the literature. Inconsistent with expectations, the reforms initiated in different countries to improve quality of selected financial information did improve value relevance in only some countries.